Adult respiratory distress syndrome in Leptospira canicola infection. Issue 6290 (22nd August 1981) - Zaltzman, M; Kallenbach, J M; Goss, G D; Lewis, M; Zwi, S; Gear, J H
Abstract : A man was admitted to the Johannesburg Hospital with a history of fever, diarrhoea, and dry cough for four days. He began to produce bloodstained sputum and was found to have severe arterial hypoxaemia. Radiography showed widespread opacification over both lung fields, and the clinical and haemodynamic features were consistent with the adult respiratory distress syndrome. Serology for Leptospira canicola was positive. Despite antibiotics, supportive therapy, and ventilation the patient died. Necropsy excluded cardiac disease. This case shows that leptospirosis may cause the adult respiratory distress syndrome.